Preparation Of Cerium Doped Nickel Oxide For Lower Reduction Temperature In Carbon Monoxide Atmosphere - Norliza Dzakaria; Azizul Hakim Lahuri; Tengku Shafazila Tengku Saharuddin; Alinda Samsuri; Fairous Salleh; Wan Nor Roslam Wan Isahak; Muhammad Rahimi Yusop; Mohd Ambar Yarmo (Malaysian Journal of Analytical Sciences, 2024)
Indexed by Scopus/MyCite